From self‐assembled peptide‐ynes to peptide polyacetylenes and polydiacetylenes. Issue 5 (9th March 2018) - Marafon, Giulia; Motta, Maria Angela; Toniolo, Claudio; Moretto, Alessandro
Abstract: A set of four organogelators from an α‐amino acid derivative to a tetrapeptide, covalently linked to an acetylenic moiety, was studied in terms of polymerization efficiencies to afford peptide polyacetylenes and polydiacetylenes. Peptides were designed to improve the organogelator behavior via formation of intermolecular H‐bonding‐mediated β‐sheet networks as a function of their main‐chain length. The polymerization experiments were run under appropriate conditions for the various monomers with the aim at elucidating how the monomer self‐assembly process might influence polymer formation. Starting compounds and their corresponding polymers were characterized by a variety of spectroscopic and microscopic techniques. Abstract :